Hubungan Kadar Glukosa Darah Puasa dengan Kadar Trigliserida dalam Darah - Christyawardani, Lidwina Septie; Haiti, Margareta (Jurnal Kesehatan, 2024)
High blood glucose levels have the potential to disrupt lipid metabolism by resulting in increased levels of total cholesterol, triglycerides (TG), low-density lipoprotein (LDL), and decreased high-density lipoprotein (HDL). If the level of triglycerides in the bloodstream continues to increase, this is called hypertriglyceridemia, which can lead to atherosclerosis. This study aims to determine how blood glucose and triglyceride levels in the bloodstream are related. Researchers looked at and analyzed the influence of the independent variable on the dependent variable in this research. This research used an observational analytical design. The samples are Diploma IV Medical Laboratory Technology students at the Health Science Faculty, UKMC. There is no significant correlation between the two variables studied, as shown by the analysis of the relationship between blood glucose concentration and triglycerides, with a p-value = 0.842. This research shows no significant correlation between the variables